Efforts of Islamic and Christian Religious Education Teachers in Forming Attitudes of Tolerance - M. Isa (el-Tarbawi : Jurnal Pendidikan Agama Islam, 2025)
Religious education plays a crucial role in fostering tolerance in students, particularly in schools with diverse religions and cultures. Through teaching, familiarization, role modeling, and collaboration between teachers, religious education fosters character in students, enabling them to live harmoniously and respect differences. At Methodist Elementary School in Banda Aceh, the religious diversity of Muslim and Christian students presents a valuable educational opportunity. Despite their differing beliefs, students continue to live harmoniously and respect each other thanks to the consistent guidance and development provided by Islamic and Christian Religious Education teachers. This study aims to determine the efforts of religious teachers in instilling values ​​of tolerance and how these tolerance attitudes are implemented in the school environment. The method used is a qualitative approach with descriptive methods. Data were obtained through observation, interviews, and documentation, then analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and verification. Data validity was maintained through triangulation of methods, time, and sources to ensure the authenticity of the findings. The results of the study indicate that Islamic and Christian Religious Education teachers at Methodist Elementary School in Banda Aceh strive to instill the values ​​of tolerance through various means, including classroom learning that emphasizes the values ​​of love, empathy, and respect for differences; joint religious activities that strengthen togetherness; daily habits such as helping each other and working together; integration of tolerance values ​​in teaching materials; and regular evaluation and monitoring of student character development. The efforts made by these teachers have proven effective in building a culture of tolerance in the school environment. Through the synergy between learning, role models, and habits, Methodist Elementary School in Banda Aceh becomes a real example of tolerance-based character education practices that are able to foster a harmonious atmosphere amidst diversity.